2006
DOI: 10.1007/s00268-006-0376-y
|View full text |Cite
|
Sign up to set email alerts
|

Nerve‐Identifying Inguinal Hernia Repair: A Surgical Anatomical Study

Abstract: Based on the newly defined identification zones, peroperative identification of all inguinal nerves is possible. Further research is warranted to assess clinical feasibility of these zones and to evaluate the influence of (facultative) division, preservation or omittance of the identification of inguinal nerves on the incidence of chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 52 publications
3
49
0
5
Order By: Relevance
“…The inguinal canal is crossed by three sensory inguinal nerves: the ilioinguinal, iliohypogastric and genital branch of genitofemoral nerve [38,63].…”
Section: Neuroanatomy In Front Of Trasversalis Fasciamentioning
confidence: 99%
See 1 more Smart Citation
“…The inguinal canal is crossed by three sensory inguinal nerves: the ilioinguinal, iliohypogastric and genital branch of genitofemoral nerve [38,63].…”
Section: Neuroanatomy In Front Of Trasversalis Fasciamentioning
confidence: 99%
“…However, taking anatomical studies into consideration [63], the working group suggests to avoid removing the nerves from their natural bed as much as possible and not to remove the covering fascia (L.E. 5 G.R.D).…”
Section: Hernia (2011) 15:239-249 243mentioning
confidence: 99%
“…Fundierte Kenntnisse der Nervenanatomie sind zur postoperativen Schmerzvermeidung unverzichtbar [21,22,29]. Die Leistennerven sollten möglichst erhalten bleiben.…”
Section: Nervenmanagementunclassified
“…[7][8][9] Recent anatomic studies have elaborated the course of GFN, in an aim to remove the myth that identification of GFN is difficult. [10][11][12] The genitofemoral nerve originates from L1/L2 and pierces the iliopsoas muscle where it lies on its ventral surface. Then it divides into genital and femoral branches, proximal to the inguinal ligament.…”
Section: To the Editormentioning
confidence: 99%
“…In an anatomic study, Wijsmuller et al showed that 94% of the genital branch of GFN entered the inguinal canal laterocaudally through the internal ring in the frontal plane. 10 Then, after running through the inguinal canal at the dorsocaudal side of the spermatic cord parallel to the cremasteric artery and vein (blue line), 44% passed dorsally, 28% medially, and 22% laterally to the spermatic cord though the external ring. It is within the canal that the genital branch is at risk during spermatic cord dissection; in addition it may be caught by constriction at the internal inguinal ring or by perineural fibrosis.…”
Section: To the Editormentioning
confidence: 99%